Pengaruh Anggaran Pendapatan Belanja Daerah Terhadap Program Pengentasan Kemiskinan Di Kabupaten Aceh Selatan - Lusi Fiartini; Alisman Alisman (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2023)
South Aceh Regency has 18 scattered sub-districts, and the distribution of the sub-district population is uneven so that it has an impact on differences in the population's economy between Tapak Tuan City and other sub-districts. It is inevitable that poverty will still hit this district, according to data from the Central Statistics Agency (BPS) the poverty rate for South Aceh Regency will reach 32.700 in 2022. To help the less fortunate, the government has made efforts to provide assistance sourced from the regional expenditure revenue budget.This research was made to find out and explain the extent of the influence of regional expenditure budgets on poverty alleviation in South Aceh district. This research was conducted from January to May 2023, using the Simple Linear Regression statistical data analysis method to make it easier for researchers to get the desired results. data brought by this researcher from the Central Statistics Agency (BPS) of South Aceh RegencyThe regression coefficient obtained is 4.468E-6 with a significant value of 0.259> 0.05 where it is shown that the coefficient is positive, so what is obtained is that there is a close relationship between the regional expenditure budget and poverty, where if the APBD budget has increased then there is also an increase in poverty. From the results of R square, it is found that 77.3% of this can be used to see the magnitude of the influence. From the calculated t value of 3.197%, which means it is in the receiving area of Ha. F value count 10.220